Pemilihan Model Scrum Dalam Pengembangan Sistem Monitoring Dengan Menggunakan Metode Agile Untuk Evaluasi Clinical Pathway - Khairul Imtihan; Lalu Mutawalli; Wire Bagye (Bianglala Informatika, 2020)
Hospitals as health care institutions are always required to provide quality, effective and acute services. PERSI forms a guideline for developing service standards so that it supports more accountable and efficient hospital health services called clinical pathways. Clinical pathways are used to systematically record each intervention given to patients. In its implementation, the clinical pathway does not always work perfectly, this is caused by various things such as the lack of resources (equipment and other health facilities), also caused by the negligence of technical implementers such as doctors, nurses, nutritionists, and pharmaceuticals. The clinical pathway monitoring system is important to know the obstacles that arise. The monitoring system can support the evaluation process to be faster. In this study, the system was developed using the agile method with the scrum model. The study was conducted at Harapan Harapan General Hospital in Tegal City involving those who played a direct role in using the system, Patient Care Management (MPP). The functional test results are divided into three, the first system quality results as much as 76% according to its function. Second, the assessment of the quality of information, the value of the quality of information produced as much as 68% according to its function. The three assessments of service quality obtained results as much as 63% according to its function.